2017
DOI: 10.1074/jbc.m117.809160
|View full text |Cite
|
Sign up to set email alerts
|

O2 sensing–associated glycosylation exposes the F-box–combining site of the Dictyostelium Skp1 subunit in E3 ubiquitin ligases

Abstract: Skp1 is a conserved protein linking cullin-1 to F-box proteins in SCF (kp1/ullin-1/-box protein) E3 ubiquitin ligases, which modify protein substrates with polyubiquitin chains that typically target them for 26S proteasome-mediated degradation. In (a social amoeba), (the agent for human toxoplasmosis), and other protists, Skp1 is regulated by a unique pentasaccharide attached to hydroxylated Pro-143 within its C-terminal F-box-binding domain. Prolyl hydroxylation of Skp1 contributes to O-dependent development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…Previously, we reported that 154 Pro of TgSKP1 is hydroxylated and glycosylated and that these post-translational modifications are predicted to change the conformation of the F-box protein-binding region of TgSKP1 as they do in the social amoeba Dictyostelium discoideum when a conserved proline residue in DdSKP1 is similarly modified [22]. An O 2 -regulated prolyl hydroxylase modifies 154 Pro and under low O 2 conditions can be observed by Western blotting as a decrease in the apparent molecular weight of TgSKP1 [19, 20, 28] (Figure 1B; TgSKP1 Input Fractions).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that 154 Pro of TgSKP1 is hydroxylated and glycosylated and that these post-translational modifications are predicted to change the conformation of the F-box protein-binding region of TgSKP1 as they do in the social amoeba Dictyostelium discoideum when a conserved proline residue in DdSKP1 is similarly modified [22]. An O 2 -regulated prolyl hydroxylase modifies 154 Pro and under low O 2 conditions can be observed by Western blotting as a decrease in the apparent molecular weight of TgSKP1 [19, 20, 28] (Figure 1B; TgSKP1 Input Fractions).…”
Section: Resultsmentioning
confidence: 99%
“…Data were obtained from AB SCIEX MALDI TOF/TOF 5800 (Applied Biosystem MDS Analytical Technologies, Foster City, CA) mass spectrometer in reflector positive-ion mode. Data analysis was performed by using Data Explorer V4.5, and the assignment of glycan structure was based on the primary mass (m/z) coupled with MS/MS fragmentation profile using the Expasy database online and the glycowork bench software analysis (84, 85).…”
Section: Methodsmentioning
confidence: 99%
“…FBPs possess a 40-amino acid F-box domain that binds to the C-terminal region of Skp1 (7,8). Recent studies show that glycosylation influences the organization and range of motions of this region of Skp1, in part by hydrogen bonding along the polypeptide in cis (9). Glycosylation is regulated by PhyA, whose action on Skp1 is rate-limited by O 2 availability in the cell (6,10).…”
Section: Cells a Genomic Bioinformatics Survey Suggested That Glt1 Bmentioning
confidence: 99%
“…Structural studies of Dictyostelium Skp1 suggest that the fulllength glycan encourages an ensemble of conformations that promote interactions with at least certain FBPs (9). The trisaccharide form of Dictyostelium Skp1 exhibits intermediate interaction with two of the FBPs (6), and, if an analogous mechanism operates in Toxoplasma, this might explain why the glt1 deletion results in a growth phenotype intermediate between complete absence of the glycan and its full assembly.…”
Section: Functional Variations Between Toxoplasma Glt1 and Dictyostelmentioning
confidence: 99%